Initiation of Antiretroviral Therapy (ART) at Different Stages of HIV-1 Disease Is Not Associated with the Proportion of Exhausted CD8+ T Cells - Jensen, Sanne Skov; Fomsgaard, Anders; Larsen, Tine Kochendorf; Tingstedt, Jeanette Linnea; Gerstoft, Jan; Kronborg, Gitte; Pedersen, Court; Karlsson, Ingrid (PloS one, 2015)
CD8+ T cell-restricted immunity is important in the control of HIV-1 infection, but continued immune activation results in CD8+ T cell dysfunction. Early initiation of antiretroviral treatment (ART) and the duration of ART have been associated with immune reconstitution. Here, we evaluated whether restoration of CD8+ T cell function in HIV-1-infected individuals was dependent on early initiation of ART. HIV-specific CD107a, IFNγ, IL-2, TNFα and MIP-1β expression by CD8+ T cells and the frequency of CD8+ T cells expressing PD-1, 2B4 and CD160 were measured by flow cytometry. The frequency of CD8+ T cells expressing the inhibitory markers PD-1, 2B4 and CD160 was lower in ART-treated individuals compared with ART-naïve individuals and similar to the frequency in HIV-uninfected controls. The expression of the three markers was similarly independent of when therapy was initiated. Individuals treated before seroconversion displayed an HIV-specific CD8+ T cell response that included all five functional markers; this was not observed in individuals treated after seroconversion or in ART-naïve individuals. In summary, ART appears to restore the total CD8+ T cell population to a less exhausted phenotype, independent of the time point of initiation. However, to preserve multifunctional, HIV-1-specific CD8+ T cells, ART might have to be initiated before seroconversion.